The mediating influence of self-efficacy and self-regulation in the relationship between perfectionism and listening anxiety - Movafagh Ardestani, Elham; Barjesteh, Hamed; Dehqan, Mahmood (Frontiers in Education, 2025)
IntroductionThis study investigates the complex relationship between perfectionism and Listening Anxiety (LA) in the context of English as a Foreign Language (EFL), with a focus on the mediating roles of Listening Self-Efficacy (LS) and Self-Regulated Learning (SRL).MethodA sample of 350 EFL learners from various language institutes in Iran was selected through cluster random sampling and completed four validated questionnaires measuring SRL, LS, perfectionism, and LA. Structural Equation Modeling (SEM) was employed to analyze the data and provide detailed insights into the interrelationships among these variables.ResultsThe results revealed significant linear relationships between the variables under study. Specifically, LS, perfectionism, and SRL were found to directly influence LA, with LS and SRL serving as stronger predictors of LA than perfectionism. In terms of predictive power, SRL ranked just behind LS.DiscussionBoth SRL and LS were significant mediators in the relationship between perfectionism and LA, suggesting that learners’ self-regulation and listening self-efficacy play key roles in how perfectionism affects LA. The findings have important implications for EFL instruction: by prioritizing LS and SRL, educators can create a more supportive, enjoyable, and effective learning environment for EFL students, ultimately reducing LA.